Guangdong ATV Performing Arts Vocational College Chaoshan music culture "tide song book" construction - Fengqiang , Lin; Sondhiratna, Thanyawat (Journal of Modern Learning Development, 2024)
Chaozhou music is one of the representative elements of Chaozhou culture. Besides music, Chaozhou Opera, English songs and dances, Chaozhou embroidery, Chaozhou architecture, etc., are the iconic artistic styles of Chaozhou culture. Chaozhou music is a general term for the folk music of the Chaoshan region, which has been praised as "the right sound of China" because of its preservation of the genes of the ancient music culture of the Chinese nation. Chiu Chow music can be used independently to form music societies, or as accompaniment music in Chiu Chow theatre groups. This paper aims to discuss the efforts and achievements of Guangdong ATV Performing Arts Vocational College in the construction of Chaoshan music culture "tide song book". Through in-depth research and analysis, this paper reveals the unique charm of Chaoshan music culture and its importance in contemporary education, and puts forward some suggestions to strengthen the inheritance and innovation of Chaoshan music culture.